DESENVOLVIMENTO DE UM SISTEMA NANOESTRUTURADO CONTENDO BROMIDRATO DE GALANTAMINA - Moraes, Bruno Henrique de (2019)
Alzheimer's disease is a type of dementia that mainly affects the elderly and over the years, there has been a growing incidence of this disease due to population aging. The neurodegeneration caused by this disease is mainly supported by the amyloid hypothesis, where the deposition of amyloid beta peptide occurs, a soluble metabolite that tends to aggregate to form plaques that lead to inflammatory processes that can lead to neuronal death. The main pharmacological treatment used for Alzheimer's dementia is the use of cholinesterase inhibitor compounds, which by inhibiting the enzymes that reduce acetylcholine levels, causing an increase in the levels of this neurotransmitter, thus reducing the excretion of the precursor protein. of amyloid. Among these inhibitory compounds are galantamine, which is a reversible competitor of acetylcholinesterase and allosteric modulator of nicotinic receptors, marketed as a galantamine hydrobromide salt was the last of its category drugs to be approved by the Food and Drug Administration (FDA). To improve the pharmacodynamic characteristics of galantamine, nanotechnology was used as a strategy, where zein and PCL were used to form the polymeric matrix of the nanostructures obtained for the carriage of the active compound. For the formation of zein nanoparticles, the liquid-liquid dispersion technique and the use of casein as stabilizing agent were used, where nanoparticles were obtained with average diameter of 254.3 ± 11 nm, polydisperse index of 0.222 ± 0.001 and encapsulation efficiency of 10.2%; unlike the formulation using the PCL polymer nanoprecipitation technique, which had an average diameter of 263.2 ± 8, a distribution of 0.11 ± 0.04 and an encapsulation efficiency of 87.49%, giving continuity in the tests physicochemical characterization, stability, release in gastrointestinal fluids and morphology studies only for PCL nanoparticles, That presented good stability under different storage conditions and remained intact when submitted to gastric and intestinal fluid release assays, thus being an option for oral galantamine transport.